The microbiomes of blowflies and houseflies as bacterial transmission reservoirs. Issue 1 (December 2017) - Junqueira, Ana; Ratan, Aakrosh; Acerbi, Enzo; Drautz-Moses, Daniela; Premkrishnan, Balakrishnan N. V.; Costea, Paul; Linz, Bodo; Purbojati, Rikky; Paulo, Daniel; Gaultier, Nicolas; Subramanian, Poorani; Hasan, Nur; et al.
Abstract Blowflies and houseflies are mechanical vectors inhabiting synanthropic environments around the world. They feed and breed in fecal and decaying organic matter, but the microbiome they harbour and transport is largely uncharacterized. We sampled 116 individual houseflies and blowflies from varying habitats on three continents and subjected them to high-coverage, whole-genome shotgun sequencing. This allowed for genomic and metagenomic analyses of the host-associated microbiome at the species level. Both fly host species segregate based on principal coordinate analysis of their microbial communities, but they also show an overlapping core microbiome. Legs and wings displayed the largest microbial diversity and were shown to be an important route for microbial dispersion. The environmental sequencing approach presented here detected a stochastic distribution of human pathogens, such asHelicobacter pylori, thereby demonstrating the potential of flies as proxies for environmental and public health surveillance.